The Red Rectum (Carpet villous adenoma of the rectum) - M Farag (Journal of Surgical Case Reports, 2010)
Carpeted villous adenomas of rectum may be extensive and not suitable for transanal excision or Endoscopic mucosal resection. We present a case of such lesion extending from anorectal junction to rectosigmoid region. After biopsy and staging, this was managed by a sphincter saving procedure, i.e. a combination of transabdominal total mesorectal excision and transanal intersphincteric dissection, with acceptable functional outcome with 8 years of follow up.